Possibilities of applying achievements in change management from developed countries in Serbia - Đuretić Gordana V.; Krasulja Nevena D. (Baština, 2019)
This paper looks at the past of Serbian companies and their current position within the world economy with an assessment of the certainty / uncertainty of business, conditioned by a dynamic and complex environment. The uncertainty in Serbia about the spread of change has significantly affected the decades-long lag. The constant expectation that change would happen by itself led to a high level of demoralization and the search for a way out to preserve the existing state although it led to a further increase in entropy. In other words, organizations in Serbia did not accept the need for a proactive approach in dealing with the growing problems caused by the inexorable transition date.